(untitled) (Teología, 2018)
Among the contributions of Post-Synodal Apostolic Exhortation “Amoris Laetitia” by Pope Francis, his reflection about the spirituality of marriage stands out. First of all, starting from the environment that questions and shapes families nowadays, we will point out some of the challenges that arose from the thorough investigation about family and marriage realities along the synod. Said challenges are of great importance to reflect on the spirituality of marriage. Secondly, we will explain the characteristics of this “specific spirituality that unfolds in family life and its relationships” as described by Pope Francis himself. Finally, we will make some contributions to strengthen the spirituality of marriage and family nowadays.